Effects of antifouling booster biocide Irgarol 1051 on the structure of free living nematodes: a laboratory experiment. Issue 7 (10th June 2016) - Hannachi, Amel; Elarbaoui, Soumaya; Khazri, Abdelhafidh; D'Agostino, Fabio; Sellami, Badreddine; Beyrem, Hamouda; Gambi, Cristina; Danovaro, Roberto; Mahmoudi, Ezzeddine
Abstract : A mesocosm experiment was conducted to evaluate the effects of Irgarol on nematode diversity, composition and trophic structure. Abstract : A mesocosm experiment was conducted to evaluate the effects of Irgarol on nematode diversity, composition and trophic structure. Sediment samples were experimentally contaminated using four increasing Irgarol concentrations [I1 (11.5 ng g −1 ), I2 (35 ng g −1 ), I3 (105 ng g −1 ) and I4 (315 ng g −1 )] and compared to non-contaminated sediments (controls). Nematode diversity as the number of nematodes species ( S ) and species richness ( d ) was significantly lower in all Irgarol treatments than in the controls while the evenness ( J ′) increased significantly in I4 treated mesocosms. The nematode species composition significantly changed following Irgarol concentrations. Paracomesoma dubiun and Terschellingia longicaudata appeared as "tolerant" species to the highest Irgarol concentration. Additionally, Chromadorina germanica and Microlaimus cyatholaimoides appeared as "opportunistic" species. In contrast, Daptonema normandicum seemed to be a "sensitive" species to Irgarol contamination. Irgarol modified also the nematode trophic structure where the relative abundance of deposit feeders decreased significantly in all the treatments compared to control mesocosms and optional predators decreased only in treated mesocosms with I3. Epigrowth feeders increased significantly in treated mesocosms with I3 and I4 and the microvores increased with I1 and decreased with I4. The relative abundance of ciliate consumers appeared unaffected by the presence of Irgarol contamination. Our results open new perspectives on the potential impact of antifouling booster biocide Irgarol 1051 on nematode biodiversity and functional diversity as trophic structures.